RESPONSE OF STEVIA (Stevia rebaudiana B.) PLANLET ON ADDITION OF ORGANIC MATERIALS IN SOME CONCENTRATIONS OF MS MEDIUM - Sepdian Luri Asmono; Kumala Ayu Lestari (Jurnal Penelitian Pertanian Terapan, 2020)
This study aims to determine the response of the growth of Stevia (Stevia rebaudiana B.) plantlets in vitro on different MS media and to organic material. This study also aims to find media and organic material formulations as substitutes for growth regulators at the culture stage before acclimatization. The method used in this research is Factorial Complete Randomized Design which consists of 2 factors. The first factor is MS media concentration (½ MS and MS Full). The second factor is several types of organic matter such as young corn extract (150 ml/L), bean sprout extract (150 ml/L), and young coconut water (150 ml/  L). The results showed that explants were able to grow shoots or roots on MS Full media as well as ½ MS media. Besides, the types of organic matter also gave different responses, but from this study, it was related to coconut water and young corn extract both to stimulate the growth and root of stevia plantlets.